Jubilee Synthesis… A Review of Jerzy Myszor’s book Kościół na Górnym Śląsku. 100-lecie diecezji katowickiej 1925–2025 (Zaranie Śląskie, 2025)
Review article concerning the book: Myszor J. (2025). Kościół na Górnym Śląsku. 100-lecie diecezji katowickiej 1925-2025. Księgarnia św. Jacka (ss. 144)
Keywords: the Church in Upper Silesia; the Diocese of Katowice; anniversary; the history of the diocese; review